Influence of Seawater on the Degree of Entrainment in the Flotation of a Synthetic Copper Ore - Maldonado-Saavedra, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Froth flotation is a process in which hydrophobic particles attach to bubbles forming particle–bubble aggregates, which are transported to the top section of the cell where they overflow to form the concentrate. Particles also reach the concentrate by entrainment, which is a non-selective process that leads to low concentrate grades. The objective of this work was to study and compare the degree of entrainment measured using three methods, in fresh and seawater, and using methyl isobutyl carbinol (MIBC) and DF-250 as frothers. The experimental results indicated that the degree of entrainment decreased in seawater. Besides, water recovery was lower in the experiments with seawater regardless of the frother that was used in the experiments, which correlated with the observed low degrees of entrainment. It is proposed that the reduction of entrainment and water recovery in seawater can be explained by a reduction of air recovery and/or more bubble coalescence in the froth. It is also proposed that surfactant diffusion/convection from the lamellae to the Plateau borders in the froth is reduced in seawater, which reduces the surface tension gradients, and thus the restoring liquid flow from the Plateau borders to the lamellae. © 2020 by the authors.